Development and pilot testing of INTERVENER, a web-based tool to match barriers to the cancer continuum organization to evidence-based interventions - Isabel Mosquera; Hannah Theriault; Dominique Meunier; Partha Basu; Andre L. Carvalho (BMC Health Services Research, 2025)
Abstract Background Barriers to the cancer continuum organization and interventions to approach them have been identified; however, there is a lack of a tool matching them. Our aim was to develop a web-based tool to identify the main barriers to the process of the cancer continuum organization, and propose matched evidence-based interventions (EBI) to overcome them. Methods A questionnaire on barriers at six steps of the process of the cancer continuum organization was answered by collaborators. Each question included several options of barriers to be ranked. Barriers were organized in a framework based on the Tanahashi conceptual model, and were categorized in these dimensions: availability of services, accessibility, affordability, acceptability, user-provider interaction, governance, protocols and guidelines, information system, and quality assurance. Systematic searches were conducted on interventions for breast, cervical and colorectal cancer. Interventions were matched with the barriers they helped to overcome, and were classified in one of these groups for each barrier and cancer site: EBI as a single strategy, EBI within a multicomponent strategy, limited-evidence interventions, and macro level approaches. Barriers and interventions were matched on a web-based tool named INTERVENER, that allows the selection of up to 3 barriers for each step. It displays the visual representation of the selected barriers, the size of each dimension being proportional with the importance of that dimension as a barrier. Experts on different aspects of screening and cancer sites provided feedback on the tool. Collaborators from 41 countries worldwide tested it. Results The tool matched 81 barriers with over 60 interventions. Collaborators reported the webpage to be organized logically (N = 17, 94%) and clearly formatted (N = 15, 83%). The tool was found useful for conducting a situational analysis of the barriers to cancer screening (N = 16, 89%), facilitating discussion with stakeholders on prioritization of interventions (N = 15, 83%), and planning their implementation (N = 15, 83%). Conclusion This tool supports countries in conducting a systematic assessment of barriers, including their prioritization, and identifying EBI to overcome them, ultimately facilitating reduction of health inequalities. This tool can support governments, policymakers, managers, and healthcare providers to make better informed decisions to improve their cancer screening programmes.